The combination of physical and mental load exacerbates the negative effect of each on the capability of skilled soccer players to anticipate action. Issue 9 (3rd May 2021) - Alder, David; Broadbent, David P.; Poolton, Jamie
ABSTRACT: This study examined the impact of combining physical and mental load on the anticipatory judgements of skilled soccer players. Sixteen players completed an 11vs11 video anticipation test in four counterbalanced conditions, each separated by 7 days. The baseline condition consisted of only the anticipation test. A physical load condition required participants to complete a simulated soccer protocol on a treadmill followed by the anticipation test. A mental load condition required participants to complete a 30-min Stroop test followed by the anticipation test. Finally, in the combined load condition, participants completed the physical load protocol alongside the mentally loading Stroop task followed by the anticipation test. Response accuracy, visual search behaviour and measures of effort were assessed throughout. Response accuracy decreased in the separate physical load and mental load conditions when compared to baseline and worsened further in the combined load condition. The reduction in response accuracy across experimental conditions coincided with an increase in the number of fixations when compared to the baseline condition. It is suggested that the separate sources of load impaired the players ability to allocate sufficient resources to task-relevant information leading to a reduction in anticipatory accuracy, and this was exacerbated in the combined load condition.